Optimizing Practices, Use, Care and Services‐Antipsychotics (OPUS‐AP): A phase 2 scale‐up to 129 long‐term care (LTC) centers in Quebec, Canada: Long‐term care and ethics. (7th December 2020) - Bruneau, Marie‐Andrée; Couturier, Yves; Gilbert, Suzanne; Boyer, Diane; Ricard, Jacques; MacDonald, Tanya; Arcand, Marcel; Morin, Michèle; Tousignant, Marilyn; Rhéaume, Andrée‐Anne; Turcotte, Jean‐Philippe; Cossette, Benoit
Abstract: Background: Antipsychotics are often used for the first‐line management of behavioral and psychological symptoms of dementia (BPSD) despite risks and side effects, and with disregard for guidelines recommendations to prioritize non‐pharmacological interventions. OPUS‐AP builds on Canadian Foundation for Healthcare Improvement, Appropriate Use of Antipsychotic initiatives and previous work by the 4 university‐affiliated research centers on an aging population in Quebec. The OPUS‐AP strategy is supported by an evidence‐based approach, involving provincial clinical guidelines developed by Québec's health‐technology assessment agency, the Institut national d'excellence en santé et en services sociaux (INESSS). In phase 1 of OPUS‐AP, conducted in 24 long‐term care (LTC) centers in Quebec, Canada, antipsychotic deprescribing (cessation or dose decrease) was achieved in 85, 5% of residents in whom it was attempted (Cossette et al. JAMDA, 2019). Method: Phase 2 of OPUS‐AP was conducted in 129 LTC centres in Quebec, Canada, from April to December 2019. OPUS‐AP aims at improving resident care through increased staff's knowledge and competency, resident‐centered approaches, nonpharmacologic interventions, and antipsychotic deprescribing in inappropriate indications. OPUS‐AP is implemented through integrated knowledge translation and mobilization activities. Antipsychotic, benzodiazepine, antidepressant prescriptions and BPSD were evaluated every 3 months for 6 months. Result: At baseline, 10, 601 residents were admitted on OPUS‐AP participating wards from which 74% had a diagnosis of major neurocognitive disorder (MNCD) and 47% an antipsychotic prescription. The follow‐up cohort included 4, 087 residents with both MNCD and antipsychotic prescription. Among the 1216 residents in whom antipsychotic deprescribing was attempted between baseline and 6 months and still included at 6 months, successful deprescribing was achieved in 85.6% (cessation 50.0% or dose decrease 35.6%). No increase in benzodiazepine or antidepressant prescriptions nor worsening of BPSD were observed. Conclusion: Phase 2 of OPUS‐AP confirmed phase 1 results of successful antipsychotic deprescribing with scale‐up to 129 LTC centers. Phase 3 of OPUS‐AP is underway in 2020 in all of Quebec's 341 public LTC centers.